The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/0907676x.2021.1900305
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of speech rhythm and heart rate as indicators of stress on student interpreters

Abstract: Stress is assumed to be intrinsic to interpreting and the ability to manage it a presumed predictor of performance. And yet, empirical research on the role of stress in interpreting has remained scarce. This study explores the impact of stress and anxiety on the academic scores, heart rate (HR) and speech rhythm of 23 student interpreters in a liaison interpreting task. Participants' stress and anxiety are measured using HR measures and the STAI test. Their speech rhythm is automatically analyzed through diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Research on the unobtrusive measurement of team members' physiological parameters (biosignals) suggests that an additional source of data can provide valuable information about team processes and unobservable states, such as stress levels, and allow objective assessments of relevant parameters in real time: team physiological dynamics (Kazi et al, 2021;Hałgas et al, 2022). This endeavor is in line with the growing recognition of the multidimensional nature of effective teamwork, highlighting the benefits of considering both visible behaviors and underlying physiological responses (Rojo López et al, 2021). By monitoring physiological signals such as HRV, researchers can assess the arousal, attention, and emotional states of team members during training or real-life scenarios.…”
Section: Traditional and Novel Evaluation Approachesmentioning
confidence: 82%
See 1 more Smart Citation
“…Research on the unobtrusive measurement of team members' physiological parameters (biosignals) suggests that an additional source of data can provide valuable information about team processes and unobservable states, such as stress levels, and allow objective assessments of relevant parameters in real time: team physiological dynamics (Kazi et al, 2021;Hałgas et al, 2022). This endeavor is in line with the growing recognition of the multidimensional nature of effective teamwork, highlighting the benefits of considering both visible behaviors and underlying physiological responses (Rojo López et al, 2021). By monitoring physiological signals such as HRV, researchers can assess the arousal, attention, and emotional states of team members during training or real-life scenarios.…”
Section: Traditional and Novel Evaluation Approachesmentioning
confidence: 82%
“…All of the listed measures ( Figure 1 ) have already received some attention in research on team performance assessment in different domains ( Elkins et al, 2009 ; Guastello and Peressini, 2017 ). For example, there is evidence suggesting that team performance correlates with movement patterns ( Calabrese et al, 2021 ) and several physiological measures such as EDA ( Pijeira Díaz et al, 2016 ), ECG ( Rojo López et al, 2021 ), eye-tracking ( He et al, 2021 ), as well as attention ( Mahanama et al, 2022 ). In the majority of these papers, team performance has been inferred using 1–2 measures, although the use of multiple modalities in one measurement would likely add value to the evaluation of team performance ( Hałgas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Rojo & Naranjo (2021) show that negative affect and stress levels of translation students were higher after simply reading an emotionally charged text than after translating it. Other studies, such as Rojo, Cifuentes & Espín (2021), Rojo, Foulquié, Espín &Martínez (2021), andRojo, Cifuentes & have shown that attention focus while translating can also modulate the participants' physiological response to emotional stress (e.g., cortisol or heart rate).…”
Section: Interpreting Into the B Languagementioning
confidence: 97%
“…Most of the studies on the effects of time pressure which have used physiological and self-reported measures have focused on interpreting (e.g., Korpal, 2016;Korpal & Jankoviak, 2021;Rojo López, Foulquié-Rubio, Espín López, & Martínez Sánchez, 2021) whereas scarce research attention has been paid on written translation. Over the last two decades, translation research, mainly through key-logging and eye-tracking instruments, has investigated its role on the different translation stages (Jensen 1999(Jensen , 2000, translators' fixations on source and target texts (Sharmin et al, 2008), and written translation product quality (De Rooze, 2003;Ghobadi et al, 2017;Kourouni, 2012), results up to date being far from conclusive.…”
Section: Time Pressure In Translationmentioning
confidence: 99%